Indological Studies in Croatia - Ježić, Mislav (2007)
History of Croatian Indology from Paulinus a Sancto Bartholomaeo to modern times. Courses of Sanskrit at Zagreb University since 1874, study of Indology founded by Radoslav Katičić in 1960, research fields of Croatian Indologists, publications, projects, Dubrovnik International Conference on the Sanskrit Epics and Puranas.
Projekt MZOS
ENG